Epigenetic downregulation of human disabled homolog 2 switches TGF-beta from a tumor suppressor to a tumor promoter. - Hannigan, A; Smith, P; Kalna, G; Lo Nigro, C; Orange, C; O'Brien, D; Shah, R; Syed, N; Spender, L; Herrera, B; Thurlow, J; Lattanzio, L; et al. (2010)
The cytokine TGF-beta acts as a tumor suppressor in normal epithelial cells and during the early stages of tumorigenesis. During malignant progression, cancer cells can switch their response to TGF-beta and use this cytokine as a potent oncogenic factor; however, the mechanistic basis for this is poorly understood. Here we demonstrate that downregulation of disabled homolog 2 (DAB2) gene expression via promoter methylation frequently occurs in human squamous cell carcinomas (SCCs) and acts as an independent predictor of metastasis and poor prognosis. Retrospective microarray analysis in an independent data set indicated that low levels of DAB2 and high levels of TGFB2 expression correlate with poor prognosis. Immunohistochemistry, reexpression, genetic knockout, and RNAi silencing studies demonstrated that downregulation of DAB2 expression modulated the TGF-beta/Smad pathway. Simultaneously, DAB2 downregulation abrogated TGF-beta tumor suppressor function, while enabling TGF-beta tumor-promoting activities. Downregulation of DAB2 blocked TGF-beta-mediated inhibition of cell proliferation and migration and enabled TGF-beta to promote cell motility, anchorage-independent growth, and tumor growth in vivo. Our data indicate that DAB2 acts as a tumor suppressor by dictating tumor cell TGF-beta responses, identify a biomarker for SCC progression, and suggest a means to stratify patients with advanced SCC who may benefit clinically from anti-TGF-beta therapies.